Case Report: Pathological Complete Response in a Lung Metastasis of Phyllodes Tumor Patient Following Treatment Containing Peptide Neoantigen Nano-Vaccine - Sha, Huizi; Liu, Qin; Xie, Li; Shao, Jie; Yu, Lixia; Cen, Lanqi; Li, Lin; Liu, Fangcen; Qian, Hanqing; Wei, Jia; Liu, Baorui (Frontiers in Oncology, 2022)
Some of the mutant peptides produced by gene mutation transcription and translation have the ability to induce specific T cells, which are called new antigens. Neoantigen-based peptide, DNA, RNA and dendritic cell vaccines have been used in the clinic. In this paper, we describe a lung metastasis of phyllodes tumor patient demonstrating pathological complete response following treatment containing personalized multi-epitope peptide neo-antigen nano-vaccine. Based on whole exome sequencing (WES), RNA sequencing and new antigen prediction, several mutated peptide fragments were predicted to bind to the patient’s HLA allotypes, including ten peptides with high predicted binding affinity for six genes. The pulmonary metastases remained stable after the four cycles of anti-PD1 and Anlotinib. After the addition of the multi-epitope peptide neo-antigen nano-vaccine, the tumor began to collapse, contracture, accompanied by a decrease of tumor markers to normal, and complete pathological remission was achieved. Using with vaccination, rhGM-CSF was used every time and low dose cyclophosphamide was injected every three weeks to improve efficacy. Peripheral blood immune monitoring demonstrated immune reactivity against a series of peptides, with the most robust post-vaccine T-cell response detected against the HLA-DRB1*0901-restricted SLC44A5 V54F peptide.